Studia historyczno-społeczne: Prace dedykowane Profesorowi Zenonowi Piechowi w siedemdziesiątą rocznicę urodzin (Księgarnia Akademicka Publishing, 2024)
In an article dedicated to antiquity, Przemysław Kmiecik reconstructs Theodoric the Great’s views on late antiquity circus spectacles based on selected fragments of Variae by Cassiodorus, chancellor of the Ostrogothic kings. Tomasz Szymczyk refers to the Middle Ages and presents the image of Peter Abelard – philosopher, theologian and pioneer of scholasticism, which emerged from Gesta Friderici, written by Bishop Otto of Freising. Katarzyna Walczyk discusses the early modern period in her work and shows how the image of Jane Grey, the Queen of England, was presented in the historiography and literature of the sixteenth century. Karolina Wójcik demonstrates a broad view of the Inca tradition and its influence on the national identity of Peruvians. The monograph further contains Szymon Orzoł’s analysis of selected themes of the 19th-century economic thought of Eugen von Böhm-Bawerk, one of the fathers of the Austrian school of economics, who critiqued Marxism from a free-market perspective. In one of the articles about 20th-century subjects, Mateusz Matysiak reconstructs the political thought of the syndicalist Kazimierz Zakrzewski, looking at it from a Nietzschean perspective. Piotr Ruciński discovers the legacy of Jan Kwieciński, a little-known publicist whose most significant achievement was a utopian political programme for the restoration of Poland and the world before the Second World War, while Mateusz Musiał identifies key features in the complexity of Turkish-Russian relations in the years 2002-2016. The Annex is a final report by Tomasz Kisiel, President of The Jagiellonian University Scientific Society of History Students (KNHS UJ) in the 2016/2017 term.